Efficient Implementation of a Demultiplexer - wason, Saksham; kumar, piyush; rathi, shubham (IJRDO -Journal of Computer Science Engineering, 2015)
This paper will address you about the basic function of the multiplexer (mux) and demultiplexer (demux), the typical application of the mux and demux, It also address you about the A 4 to 1 mux and demux [ designed with Small Scale Integration(SSI), A 4 to 1,8 to 1, 16 to 1 Medium Scale Integration ]. A Multiplexer is a device that selects one of several analog or digital input signals and forwards the selected input into a single line. Demultiplexer is a device taking a single input signal and selecting one of many data-outputlines, which is connected to the single input.